Leading cases in the law of banking - Chorley, Lord; Smart, P. E. (London : Sweet & Maxwell, 1977)
This book highlights legal decision cases under the auspices of the council of the institute of bankers, with importance attached to the finance of foreign trade in the business of banking.
Includes index.
asm; 21/10/19
Loans
Keywords: Banking law